Exploring the Perceptions of Private Hospitals on the Adoption of Activity-based Costing (ABC) - John Ernest B. Aguilar; Ayra Mae T. Pelenio; Aiza L. Tapia; Eligen H. Sumicad Jr. (Journal of Accounting and Finance in Emerging Economies)
Purpose: To investigate the perception of private hospitals on taking ABC as a tool to recognize and assign costs.